Starting a Foreign Investment across Sectors - De la Medina Soto, Christian; Ghossein, Tania (World Bank, Washington, DC, 2014)
The ease of starting a foreign investment in various sectors is a relevant consideration for investors seeking to establish an investment project abroad. Two thematic areas will be analyzed in this paper to answer the following questions: Which economies impose equity ownership restrictions on foreign investors and which procedural barriers do foreign companies face when establishing foreign-owned subsidiaries in these economies? The analysis is based on findings from the Foreign Direct Investment Regulations indicators, which measure 103 economies, on whether they restrict foreign ownership across economic sectors and on the establishment process they impose on foreign-owned companies. Nearly 80 percent of the economies covered in the Foreign Direct Investment Regulations database restrict foreign companies from entering in some sectors of their economies. In addition, establishing a foreign-owned company takes longer and requires more steps than starting a domestically-owned company in 94 percent of the economies observed. Overall, economies in Eastern Europe and Central Asia and high-income OECD economies have fewer equity restrictions on foreign ownership than economies in the other regions and require the least number of additional procedures of foreign companies to establish a subsidiary. The findings are significantly correlated with inflows of foreign direct investment on a per-capita basis.